Degreasing the wheels of finance - Aleksander Berentsen; Samuel Huber; Alessandro Marchesiani (University of Zurich, Department of Economics, 2012)
Can there be too much trading in financial markets? To address this question, we construct a dynamic general equilibrium model, where agents face idiosyncratic preference and technology shocks. A financial market allows agents to adjust their portfolio of liquid and illiquid assets in response to these shocks. The opportunity to do so reduces the demand for the liquid asset and, hence, its value. The optimal policy response is to restrict (but not eliminate) access to the financial market. The reason for this result is that the portfolio choice exhibits a pecuniary externality: An agent does not take into account that by holding more of the liquid asset, he not only acquires additional insurance but also marginally increases the value of the liquid asset which improves insurance for other market participants.
Keywords: E52; E58; E59; 330; monetary policy; liquidity; financial markets